(untitled) (Community Based Medical Journal, 2025)
Mobile learning has been used increasingly in the past decades in different health profession education, and advancement in technology have produced different forms of mobile learning development modalities such as simulations, virtual patients, online courses and many interactive contents. However, many of those efforts’ outcomes failed to live up to their promises; hence, those were not widely adopted and became unsustainable. A literature review has been done through a literature search conducted across three databases – Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE (Ovid) and Google scholar – for studies describing or evaluating different mobile learning platform as used for education and professional development of different health professions based on user experience, perceived barriers, facilitating factors to scale it up and make it sustainable. This paper tends to identify factors or actions which are considered to optimize the experience and satisfaction of different stakeholders, help scaling up and identify strategies for sustainability of mobile learning interventions for health professions education. CBMJ 2025 January: Vol. 14 No. 01 P: 186-191